2023
DOI: 10.48077/scihor.26(2).2023.19-30
|View full text |Cite
|
Sign up to set email alerts
|

Formation of seed potato yield depending on the elements of cultivation technology

Abstract: It is possible to realise the maximum genetic potential of modern potato varieties by improving the elements of agricultural technology, in particular, optimising plant nutrition, which determines the relevance of this study. The purpose of the study was to substantiate the specific features of potato productivity formation depending on the elements of growing technology in Forest-Steppe conditions. Field studies were conducted during 2019-2021 on chernozem soils. The features of growth and development of pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…found that this indicator was reducing while the plants were growing and developing as a result of lodging. This phenomenon was caused by a group of biotic and abiotic factors of the environment (Kalenska, Suddenko, 2016;Myronova et al, 2023). Thus, during the period of ripening plant density was reducing and was 254.1±2.6 to 275.0±2.7 plants per m 2 by the trial variants.…”
Section: Resultsmentioning
confidence: 99%
“…found that this indicator was reducing while the plants were growing and developing as a result of lodging. This phenomenon was caused by a group of biotic and abiotic factors of the environment (Kalenska, Suddenko, 2016;Myronova et al, 2023). Thus, during the period of ripening plant density was reducing and was 254.1±2.6 to 275.0±2.7 plants per m 2 by the trial variants.…”
Section: Resultsmentioning
confidence: 99%
“…Раціональне застосування хімічних та біологічних препаратів у насадженнях смородини чорної залежить від природних ентомофагів, які безпосередньо збалансовують біологічну рівновагу, призводять до збереження високоякісного врожаю [16,17,18,19,20].…”
Section: вступunclassified